Congenital hepatic hemangioma: an unusual case report of pulmonary hypertension - Qianqin Zhou; Juan Jiang; Yinquan Xu; Hanyan Qiu; Xiaoyan Wen; Shaoqi He; Qin Lv (BMC, 2023)
Abstract Background Pulmonary hypertension (PH) in newborns is a rare but serious condition that often requires immediate intervention and quick diagnosis of the correct etiology to prevent mortality. Congenital hepatic hemangioma (CHH) is an example of an extrathoracic etiology of PH. Case presentation Herein, we report the case of a newborn with a giant liver hemangioma, who presented with an early onset of PH and was successfully treated with intra-arterial embolization. Conclusions This case illustrates the importance of suspicion and prompt evaluation of CHH and related systemic arteriovenous shunts among infants with unexplained PH.